Pelatihan Perhitungan Break event Point (BEP) pada Usaha Kapal Arumbae di Desa Laha Kota Ambon - Deby M Kewilaa (Komunitas: Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
Break-even point analysis is conducted to assess a company's performance, providing insight into the importance of financial bookkeeping and economic analysis. It can also be used as a consideration for entrepreneurs in making decisions related to sales activities. Break-even point refers to a concept used in financial planning to determine the level of sales or revenue required to cover all costs and expenses, resulting in zero profit or loss. The PKM training is conducted in three stages: the preparation stage, where an initial survey is conducted to determine participants' knowledge of the Break-Even Point (BEP) calculation. The implementation stage, where training is provided to all fishermen on the BEP calculation. The monitoring and evaluation stage, where the implementation of the BEP calculation is monitored and the fishermen's understanding of the break-even point is evaluated. Break-even point (BEP) training is expected to improve business owners' and crew members' understanding of the BEP concept and enable them to apply BEP calculations in decision-making.